Makrodaten: Die amtliche Statistik stärken - Ruediger Bachmann; Almut Balleer; Zeno Enders; Niklas Garnadt; Heiko Stüber (Wirtschaftsdienst, 2023)
– Despite some progress, German macroeconomists are generally dissatisfied with access to important data in Germany. Legal, technical and organisational obstacles abound, in particular as far as mergers of data sets from heterogeneous sources are concerned. This article suggests a number of concrete measures, including legal changes, to improve the situation. Easy access to a variety of data sources is a necessary condition for the design, evaluation, and thus, for the improvement of macroeconomic policies. Better informed decisions are also less prone to be influenced by lobbyists.
Keywords: E00; K39; C80; 330